Who Are Hospice Patients and What Care Is Provided in Hospices? A Pilot Study - Koorn, Remco M. (Am J Hosp Palliat Care, 2019)
BACKGROUND: Hospices provide multidimensional care. In the Netherlands, patients with <3 months estimated life expectancy have access to hospice care. Insight into patients admitted to hospices and the care provided is lacking. In preparation for a national multicenter study, a pilot study was performed. OBJECTIVE: The primary objective was to test the appropriateness of the study procedures and the availability of hospice patient records (HPRs), and patient and care characteristics. METHOD: A cross-sectional pilot study was performed using a descriptive exploratory design. Sixteen hospices were invited to participate, and HPRs from 8 deceased patients per hospice were selected. Data were collected using self-developed electronic case report forms. OUTCOMES: (1). Appropriateness of procedures: availability of HPRs and identified barriers and strategies. (2) Availability of patient and care characteristics in HPRs. RESULTS: In total, 104 HPRs of patients from 13 hospices were enrolled. Various types of HPRs were found with different availabilities: nurses’ records were most available (98%) compared to volunteers’ records (62%). Overarching barriers were as follows: ethical issues, lack of knowledge, and lack of communication. Information about the illness was most available (97%), whereas descriptions of experienced symptoms were least available (10%). CONCLUSION: Collecting HPRs is difficult and time-consuming. Specifically, data from separate records of home care nurses and general practitioners were difficult to come by. Patient and care characteristics were alternately present, which led to an extension of data collection in HPRs to 3 time periods. Piloting is essential to adjust study procedures and outcome measures to ensure a feasible national multicenter hospice study.